A EDUCAÇÃO COMO COMMODITY: A POLÍTICA DE ORGANISMOS INTERNACIONAIS - Eduard Angelo Bendrath (Universidade do Oeste Paulista, 2008)
This article aims to discuss the overall picture of education as the prism of the multilateral organizations of direct influence on regional policies, especially in developing countries. The concept of education as a business sector and opening up foreign investment in education by the WTO, World Bank and IMF, is an abrupt change in educational relations and set the foundations for an educational exclusion increasingly in developing countries. The role of UNESCO and its representation as a legitimate international authority in partnership with the World Bank put in doubt the real interests of the goals of both institutions in the world and the direct consequences of this relationship in the education field. And what can we expect of education policies based on international agreements with funding agencies? Education as commodity will be the future?